Development of novel benzofuran-isatin conjugates as potential antiproliferative agents with apoptosis inducing mechanism in Colon cancer. (1st January 2021) - Eldehna, Wagdy M.; Salem, Rofaida; Elsayed, Zainab M.; Al-Warhi, Tarfah; Knany, Hamada R.; Ayyad, Rezk R.; Traiki, Thamer Bin; Abdulla, Maha-Hamadien; Ahmad, Rehan; Abdel-Aziz, Hatem A.; El-Haggar, Radwan
Abstract: In the current work, a new set of carbohydrazide linked benzofuran-isatin conjugates (5a–e and 7a–i ) was designed and synthesised. The anticancer activity for compounds (5b–d, 7a, 7b, 7d and 7g ) was measured against NCI-55 human cancer cell lines. Compound 5d was the most efficient, and thus subjected to the five-dose screen where it showed excellent broad activity against almost all tested cancer subpanels. Furthermore, all conjugates (5a–e and 7a–i ) showed a good anti-proliferative activity towards colorectal cancer SW-620 and HT-29 cell lines, with an excellent inhibitory effect for compounds 5a and 5d (IC50 = 8.7 and 9.4 µM (5a ), and 6.5 and 9.8 µM for (5d ), respectively). Both compounds displayed selective cytotoxicity with good safety profile. In addition, both compounds provoked apoptosis in a dose dependent manner in SW-620 cells. Also, they significantly inhibited the anti-apoptotic Bcl2 protein expression and increased the cleaved PARP level that resulted in SW-620 cells apoptosis. Graphical Abstract: UF0001